Enhancing positive mood in older adults: implications for vaccine effectiveness - Carlisle, Sophie (2022)
The influenza vaccine is less effective in older adults compared to their younger counterparts. At the same time, this population is more susceptible to contracting influenza, with more severe consequences, including higher rates of complications, hospitalisations, and deaths. There is an abundance of evidence demonstrating how psychological factors, such as stress, can influence and modulate immune function, including response to vaccinations. Recent work has extended this to other psychological factors, suggesting that mood, or affect, may also be linked to vaccine response, however the evidence here is much more limited. This thesis presents three inter-related pieces of research, which sought to build on this evidence base and contribute to our current understanding of the influence of mood on vaccinations. The ultimate aim of this research was to develop an intervention to enhance positive mood, with a view to enhancing the effectiveness of the influenza vaccination in the older adult population.